A selection breeding pattern for sexually dimorphic breast plumage color in Guangxi Yao chickens - Jianbo Li; Rifu Wu; Yan Wang; Jie Ma; Zhi Peng; Wei Luo; Tianfei Liu; Dingming Shu; Hao Qu (Poultry Science, 2024)
ABSTRACT: The breast plumage color of Guangxi Yao chickens shows obvious sexual dimorphism, with roosters showing black and black with red, and hens displaying partridge and red. Black plumage in roosters is considered a sign of quality, necessitating the purification of plumage color. Here, we developed an effective method based on genetic variations within MC1R and plumage characteristics. We clarified the distribution of 5 single nucleotide polymorphisms (SNP) and 3 haplotypes (H1, H2, and H3) of MC1R gene, and revealed potential associations between haplotype H1 and black breast plumage in the F2 resource population derived from a backcross between Guangxi Yao and Yellow chickens. Subsequently, using H1/H1 diplotype roosters and hens to construct families (n = 1,244) notably increased the proportion of offspring with black plumage. Further analysis suggested that red plumage in hens may be the putative phenotype of black plumage in roosters, driven by haplotype H1 of the MC1R gene, as verified by genotype and phenotype analysis. As expected, we found that almost all male offspring of hens with red breast plumage showed black plumage. In short, we established a selection pattern based on the combination of black-plumage roosters and red-plumage hens can significantly purify the sexually dimorphic plumage color and improve the efficiency of breeding programs in Guangxi Yao chickens. Our findings provide a novel technical framework to accelerate the breeding process for plumage trait in poultry.